Virtual screening and directional preparation of xanthine oxidase inhibitory peptides derived from hemp seed protein - Xiaoni Huang; Jiajun Liao; Ping Shi; Xiaodong Pei; Chenghua Wang (Food Science and Human Wellness)
The traditional nutritional and medical hemp (Cannabis sativa L.) seed protein were explored for the discovery and directional preparation of new xanthine oxidase inhibitory (XOI) peptides by structure-based virtual screening, compound synthesis, in vitro bioassay and proteolysis. Six subtypes of hemp seed edestin and albumin were in silico hydrolyzed by 29 proteases, and 192 encrypted bioactive peptides were screened out. Six peptides showed to be XOI peptides, of which four (about 67%) were released by elastase hydrolysis. The peptide DDNPRRFY displayed the highest XOI activity (IC50 = (2.10 ± 0.06) mg/mL), acting as a mixed inhibitor. The pancreatic elastase directionally prepared XOI hemp seed protein hydrolysates, from which 6 high-abundance XOI peptides encrypted 3 virtually-screened ones including the DDNPRRFY. The novel outstanding hemp seed protein-derived XOI peptides and their virtual screening and directed preparation methods provide a promising and applicable approach to conveniently and efficiently explore food-derived bioactive peptides.